2017
DOI: 10.1038/s41598-017-11433-4
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical and photoelastic properties of 3D printable stress-visualized materials

Abstract: Three-dimensional (3D) printing technology integrating frozen stress techniques has created a novel way to directly represent and characterize 3D interior discontinuities and the full-field stress induced by mining- or construction-related disturbances of deeply buried rock masses. However, concerns have been raised about the similitude between the mechanical behaviours of the printed model and its prototype rock mass. Ensuring the mechanical properties of the printable materials are as close as possible to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 49 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…Nowadays, with 3D printing one can replicate the diversified geometry encountered in a soil at a resolution of few micrometres. However, only a few studies have shown the potential of using 3D prints to better understand physical, mechanical or biological processes in soils (Dal Ferro & Morari, 2015; Otten et al, 2012; Ozelim & Cavalcante, 2019; Wang et al, 2017). X‐ray CT imaging of 3D printed structures using different printing techniques revealed imperfections, such as clogging of parts of the pore space by printing material residues or printing‐aid material, which would introduce artefacts into the physical functioning (Bacher, Schwen, & Koestel, 2015; Dal Ferro & Morari, 2015; Watson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, with 3D printing one can replicate the diversified geometry encountered in a soil at a resolution of few micrometres. However, only a few studies have shown the potential of using 3D prints to better understand physical, mechanical or biological processes in soils (Dal Ferro & Morari, 2015; Otten et al, 2012; Ozelim & Cavalcante, 2019; Wang et al, 2017). X‐ray CT imaging of 3D printed structures using different printing techniques revealed imperfections, such as clogging of parts of the pore space by printing material residues or printing‐aid material, which would introduce artefacts into the physical functioning (Bacher, Schwen, & Koestel, 2015; Dal Ferro & Morari, 2015; Watson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The strength and elastic modulus are lower than those of the natural Berea sandstone under frozen‐stress temperature, which is a significant challenge for the study of rock mechanics using 3‐D printing techniques. Though some progress has been made to narrow the gap (Wang et al, ), further improvement is still needed. Considering the aim of this study, we intend to discuss this issue in our follow‐up study.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic bands of aliphatic C-H asymmetric and symmetric stretching are in the range from 2956 to 2873 cm −1 . This indicates that the Tango+ material used in this study is a polyurethane acrylate [13,15].…”
Section: Chemical Composition Analysis Via Ir Spectroscopymentioning
confidence: 99%